A Dyadic Growth Modeling Approach for Examining Associations Between Weight Gain and Lung Function Decline: The NHLBI Pooled Cohorts Study. Issue 10 (14th April 2020) - Cornelius, Talea; Schwartz, Joseph E; Balte, Pallavi; Bhatt, Surya P; Cassano, Patricia A; Currow, David; Jacobs, David R; Johnson, Miriam; Kalhan, Ravi; Kronmal, Richard; Loehr, Laura; O'Connor, George T; et al.
Abstract: The relationship between body weight and lung function is complex. Using a dyadic multilevel linear modeling approach, treating body mass index (BMI; weight (kg)/height (m) 2 ) and lung function as paired, within-person outcomes, we tested the hypothesis that persons with more rapid increase in BMI exhibit more rapid decline in lung function, as measured by forced expiratory volume in 1 second (FEV1 ), forced vital capacity (FVC), and their ratio (FEV1 :FVC). Models included random intercepts and slopes and adjusted for sociodemographic and smoking-related factors. A sample of 9, 115 adults with paired measurements of BMI and lung function taken at ≥3 visits were selected from a pooled set of 5 US population-based cohort studies (1983–2018; mean age at baseline = 46 years; median follow-up, 19 years). At age 46 years, average annual rates of change in BMI, FEV1, FVC, and FEV1 :FVC ratio were 0.22 kg/m 2 /year, −25.50 mL/year, −21.99 mL/year, and −0.24%/year, respectively. Persons with steeper BMI increases had faster declines in FEV1 ( r  = −0.16) and FVC ( r  = −0.26) and slower declines in FEV1 :FVC ratio ( r  = 0.11) (all P  values < 0.0001). Results were similar in subgroup analyses. Residual correlations were negative ( P  < 0.0001), suggesting additional interdependence between BMI and lung function. Results show that greater rates of weight gain are associated with greater rates of lung function loss.